Effect of gamma interferon on phospholipid hydrolysis and fatty acid incorporation in L929 cells infected with Rickettsia prowazekii. - Winkler, H H (1993)
Treatment of Rickettsia prowazekii-infected L929 cells with gamma interferon (IFN-gamma) immediately after infection altered the lipid metabolism of the host cells as determined by measurement of phospholipid hydrolysis and oleic acid incorporation into phospholipids and neutral lipids. At 48 h postinfection, there was increased phospholipid hydrolysis in infected cultures relative to mock-infected cultures and a further increase in radiolabeled phospholipid hydrolysis in IFN-gamma-treated infected cultures. Oleic acid, the radiolabeled product of hydrolysis, was found in both the free fatty acid and neutral lipid fractions. None of the mock-infected cultures demonstrated increased hydrolysis of their radiolabeled phospholipids in response to treatment with IFN-gamma. Most of the radiolabeled oleic acid incorporated into cultures in the interval between 24 and 48 h after infection and IFN-gamma treatment was present in the phospholipid fraction. However, the neutral lipid fraction from the infected cultures that had been IFN-gamma treated was labeled to a greater extent than that from the untreated cultures. Thin-layer chromatographic analysis of the neutral lipid fractions from both the hydrolysis and incorporation experiments demonstrated that most of the radiolabel was in triglycerides. The infected cultures at 30 h were intact as assessed by the exclusion of trypan blue, but at 48 h postinfection in the IFN-gamma-treated infected cultures more than half of the cells were unable to exclude trypan blue. In no case did the mock-infected cells show substantial damage as a result of IFN-gamma treatment.